Improving radiation therapy for non-small cell lung cancer: molecular imaging and a team-based approach - Everitt, SJ (Department of Biomedical Imaging, Faculty of Medicine, University of Malaya, Malaysia, 2007)
The successful integration of molecular imaging and radiation therapy has been shown to significantly impact the management of patients with non-small cell lung cancer (NSCLC). The collaboration of multidisciplinary team members, including radiation oncologists, radiation therapists, nuclear medicine physicians and physicists, has enabled PET/CT to be utilised for routine use throughout the radiotherapy treatment trajectory. Applications include disease diagnosis and staging, target volume definition for radiation therapy and monitoring tumour response to treatment. Not only has the adoption of this technology demonstrated benefits for our current patients, it is also opening doors for significant research in the future.